Transforming urban nightlife and the development of smart public spaces - Abusaada, Hisham, 1956-; Elshater, Abeer, 1976-; Rodwell, Dennis (Advances in civil and industrial engineering (ACIE) book series., 2021)
"This book investigates urban nightlife transformations and the challenge of enhancing the sense of belonging in sensitive areas like local communities and historical sites and offers new insights into controlling the chaotic intervention of traditional or digital technology, whether from citizens themselves or local authorities"--